(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present work aims to develop and validate a simple, rapid, and reproducible reverse phase ultra-fast liquid chromatography method with a UV detector (RP-UFLC-UV) was developed for the separation and determination of sitagliptin (STG) enantiomers (S-(STG) and R-(STG)) simultaneously. Baseline separation was achieved on Lux cellulose-1 column, (cellulose tri-(3,5-dimethyl phenyl carbamate (Chiralcel OD-RH, 250 mm × 4.6 mm, 5 μm) column and mobile phase consisted of 20mM borate buffer solution (pH = 9±0.05) and ACN in the ratio of (60:40, v/v) at a flow rate of 0.8 mL/min was used. Detection of peaks was monitored at 262 nm. For analyzing the STG enantiomers in the rat serum and pure API, a method was developed using the chiral RP-UFLC-UV method was validated. The single oral dose of 2.5 mg/kg of STG racemate was administered to a group of 6 healthy rats for a comparative pharmacokinetic study of both the enantiomers. The linear range of the calibration curve for each enantiomer was 0.5–64 μg/mL. The precision of this method at concentrations between 0.5–48 μg/mL was within 8.65% and the % recovery (accuracy) of both sitagliptin (STG) enantiomers (S-(STG) and R-(STG) were 98.47–101.02% and 98.93-100.52%. The precision at LLOQ (0.5 μg/mL) was between 8.65%-7.09%, which was poor than that at QC levels, and the average extraction recovery was higher than 85% for both sitagliptin (SGT) enantiomers at QC levels, and its pharmacokinetics of enantiomers was found to be stereoselective.